2021
DOI: 10.1101/2021.03.26.21254415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smoking Interaction with a Polygenic Risk Score for Reduced Lung Function

Abstract: Importance: Risk to airflow limitation and Chronic Obstructive Pulmonary Disease (COPD) is influenced by combinations of cigarette smoking and genetic susceptibility, yet it remains unclear whether gene-by-smoking interactions contribute to quantitative measures of lung function. Objective: Determine whether smoking modifies the effect of a polygenic risk score's (PRS's) association with reduced lung function. Design: United Kingdom (UK) Biobank prospective cohort study. Setting: Population cohort. Particip… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Furthermore, in line with previous results in the literature, we observed a significant interaction with ever-smoking and pack-years of smoking for FEV1/FVC (Kim et al, 2021;Aschard et al, 2017).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, in line with previous results in the literature, we observed a significant interaction with ever-smoking and pack-years of smoking for FEV1/FVC (Kim et al, 2021;Aschard et al, 2017).…”
Section: Resultssupporting
confidence: 92%
“…In addition, Aschard et al observed an interaction between a genetic risk score for FEV1/FVC and ever-smoking status (Aschard et al, 2017). Related, Kim et al also observed highly significant interactions between genome-wide polygenic risk scores for lung function and smoking variables (Kim et al, 2021). While detecting significant interactions on this aggregated level is encouraging, identification of individual genes and pathways is challenging based on such results.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the PRS may be associated with genetic susceptibility to environmental exposure-induced injury and consequently the rate of early lung function decline. For example, genetic factors may modify the effect of cigarette smoking on the development of COPD [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The many genomewide association studies (GWAS) of lung function measures [14][15][16][17][18][19][20][21][22][23][24][25] have implicated pathways related to lung development [20,[26][27][28], inflammation [26], and tissue repair [29], among others [29]. Lung function is also affected by environmental exposures, such as smoking [30][31][32] and air pollution [33], which can disrupt airway development in early life, increasing the risk of childhood asthma and perhaps other chronic obstructive diseases [8][9][10][11][12]34,35]. For under accession phs002921.v1.p1.…”
Section: Introductionmentioning
confidence: 99%